Agencification in the United States and Germany and What the EU Might Learn From It. Issue 2 (1st April 2016) - Chamon, Merijn
Abstract : In the European Union the legislature has, in the past years, established an increasing number of agencies, granting them increasingly important powers. This phenomenon of agencification is legally problematic because it does not have a legal basis in the EU Treaties. In order to better understand the challenges posed by EU agencification, this Article looks at similar agencification processes in two other federal-type polities, the U.S. and Germany. Germany is especially relevant to understanding the vertical (federal) dimension to EU agencification, while the U.S. experience can inform us about the horizontal (separation of powers) dimension. This is done by looking at three distinct issues: The question of the initial establishment of a new body at the EU (federal) level, the extent to which powers can be entrusted to such a body, and the degree to which the decisions adopted by such bodies are judicially scrutinized. The Article concludes that EU agencification poses a greater risk than agencification in Germany or the US because control is partially less well-established (compared to Germany) and because the EU polity is much less mature (compared to the U.S.).